ANALISIS PERLAKUAN ASET TETAP RUMAH SAKIT UMUM DAERAH (Studi Empiris pada RSUD Ratu Zalecha Martapura) - Eka Raya Hadi Kusuma (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Purpose of this research for to To know about suitability of management fixed assets at RSUD Ratu Zalecha Martapura and Financial Accounting Standards No. 16 concerning technical guidelines for BLUD financial statements This research is located at the Ratu Zalecha Martapura Regional General Hospital. Data collection was carried out by interview and data collection methods. Data analysis was performed with a model Miles and Huberman. The result of this research indicate that there is mistake of depreciation expense in the presentation, It is not disclosure yet about base marking of fixed assets, it does not deside yet capitalization policy of maintenance expense, There is fixed assets which the book value less then minimum value of capitalization in the list of fixed assets. Classification, measurement, depreciation, and disposal of fixed assets has appropriate with government accounting standart 07.